252 CHANGES IN BRAIN NATRIURETIC PEPTIDE LEVELS IN PATIENTS WITH CONGENITAL HEART DISEASE UNDERGOING CARDIAC CATHETERIZATION. (1st January 2006) - Rothman, A.; Evans, W. N.; Mayman, G. A.; Acherman, R. J.; Luna, C. F.; Restrepo, H.
Abstract : Introduction: There is little information on the changes in brain natriuretic peptide (BNP) levels during cardiac catheterization. We measured changes in BNP levels in patients with congenital heart disease (CHD) undergoing cardiac catheterization. Materials and Methods: The study included 100 patients (mostly children), 34 underwent diagnostic and 66 interventional catheterization. Diagnoses were atrial septal defect (ASD) 17, patent ductus arteriosus (PDA) 11, aortic coarctation (CoA) 11, tetralogy of Fallot 13, single ventricle 12, ventricular septal defect (VSD) 2, and other 34. Interventional procedures included ASD device closure (17), PDA device closure (4), VSD device closure (2), coil occlusion of small PDA (7), coil occlusion aorto-pulmonary collaterals (12), dilation or stenting of CoA (11), dilation or stenting of pulmonary artery (13). BNP levels were measured (in pg/mL) using the Triage® BNP Test (Biosite Labs, San Diego, CA) before, immediately after, and 1 week after cardiac catheterization. Results: BNP levels decreased immediately after CoA intervention (45.4 vs 26.7, p < .05). In the other groups, there was no significant change in BNP levels with the procedure. One week after the procedure, BNP levels were significantly higher in patients who underwent diagnostic catheterization (46.1 vs 31.0, p < .05) and device closure (of ASD, PDA, or VSD) (55.8 vs 29.0, p < .01) Only 4 of the 100 patients had a BNP level more than 100 pg/mL before the procedure. Conclusions: BNP levels are not generally elevated and do not change acutely in the majority of patients with CHD who undergo cardiac catheterization. In this study, only patients who underwent CoA intervention had an acute significant decrease in BNP levels. The increase in BNP levels 1 week after the procedure may reflect changes in patient's level of hydration.